Flexor tendon transection and post-surgical external fixation in calves affected by severe metacarpophalangeal flexural deformity - SATO, Ayano (J Vet Med Sci, 2020)
This study aimed to evaluate the transection of superficial digital flexor tendon (SDFT) and deep digital flexor tendon (DDFT) in calves with severe metacarpophalangeal flexural deformities (MPFD). The study comprised 17 forelimbs of 10 calves that were diagnosed at the Animal Medical Centre, Rakuno Gakuen University. The calves were treated via transection of the SDFT and DDFT with retention of the suspensory ligament, followed by external fixation according to a post-surgical gait test. The post-procedural prognosis was determined at 14 days post-surgery. Of the 17 limbs, 14 (82%) achieved non-lameness and a good prognosis. Surgical complications were not observed in any treated calves. The transection of SDFT and DDFT is an effective first-line surgical option for calves with severe MPFD.